The Impact of Home-Based HIV Counseling and Testing in Early Detection and HIV/AIDS Transmission Prevention within Families: A Systematic Review - Achmad Fauzi; Ninuk Dian Kurniawati; Harmayetty Harmayetty (Universitas Pahlawan Tuanku Tambusai, 2026)
Pendahuluan: Human Immunodeficiency Virus (HIV) menyerang sistem kekebalan tubuh dengan merusak sel CD4. Penularan HIV di dalam rumah tangga masih menjadi perhatian, terutama pada ibu rumah tangga dan anggota keluarga yang mungkin terpapar melalui pasangan serta memiliki keterbatasan pengetahuan tentang pencegahan HIV. Home-Based HIV Counseling and Testing (HBHCT) merupakan intervensi yang mendukung deteksi dini HIV melalui konseling dan tes HIV secara rahasia di lingkungan rumah. Tujuan: Studi ini bertujuan untuk mengkaji dampak HBHCT dalam mencegah penularan HIV/AIDS di dalam rumah tangga. Metode: Tinjauan sistematis dilakukan dengan menggunakan artikel dari PubMed, ScienceDirect, dan Scopus yang diterbitkan dalam 15 tahun terakhir. Pencarian artikel menggunakan kata kunci Home, Counseling and Testing, HIV/AIDS, dan Families. Kualitas studi dinilai menggunakan Joanna Briggs Institute critical appraisal checklist untuk studi randomized controlled trial dan kohort. Hasil: Dari 1.872 artikel yang teridentifikasi, sembilan studi memenuhi kriteria inklusi, terdiri atas delapan studi randomized controlled trial dan satu studi intervensi prospektif. Kesimpulan: HBHCT efektif dalam meningkatkan deteksi dini HIV, mengurangi stigma terkait HIV/AIDS, serta mendukung pencegahan penularan HIV di dalam keluarga. Kata Kunci: Home Based Counselling and Testing, HIV/AIDS, Keluarga Introduction: Human Immunodeficiency Virus (HIV) attacks the immune system by destroying CD4 cells. Transmission within households remains a concern, particularly among housewives and family members who may be exposed through their partners and have limited awareness of HIV prevention. Home-Based HIV Counseling and Testing (HBHCT) is an intervention that supports early HIV detection by providing confidential counseling and testing in the home setting. Objective: This study aimed to examine the impact of HBHCT on preventing HIV/AIDS transmission within households. Methods: A systematic review was conducted using articles from PubMed, ScienceDirect, and Scopus published within the last 15 years. The search used the keywords Home, Counseling and Testing, HIV/AIDS, and Families. Study quality was assessed using the Joanna Briggs Institute critical appraisal checklist for randomized controlled trials and cohort studies. Results: From 1,872 identified articles, nine studies met the inclusion criteria, consisting of eight randomized controlled trials and one prospective intervention study. Conclusion: HBHCT is effective in promoting early HIV detection, reducing HIV/AIDS-related stigma, and supporting prevention of HIV transmission within families.